Justice in the Family: A Defence of Feminist Contractarianism. - Radzik, Linda (Journal of Applied Philosophy, 2005)
Jean Hampton argues that we can detect exploitation in personal relationships by thinking about what we would agree to were we to set aside the emotional benefits we receive from those relationships. Hampton calls her account“feminist contractarianism,” but it has recently been critiqued as decidedly un-feminist, on the grounds that it is hostile to women's interests and women's values. Furthermore, Hampton's requirement that we imaginatively distance ourselves from our emotional connections to our loved ones— the key element in her contractarian test— is simply ad hoc. In this essay, I will evaluate these objections and offer a new justification for Hampton's test. I conclude that feminist contractarianism is not only a useful tool for detecting exploitation in the family, it is also deserving of its feminist label.